THE OPTIMAL FLAT PANEL SOLAR THERMOELECTRIC GEOMETRIES FOR HEAT AND ELECTRIC POWER PRODUCTION - Kazuz, Ramadan (European Scientific Journal, ESJ, 2015)
A calculation technique provides direct calculation of the heat and electric power of flat panel solar thermoelectric system is established, this was in order to determine the optimum system size optimization for combined water heating and electricity generation. The system size optimization is trade-off between the thermoelement length, cross-section area and the solar absorber size. The technique is developed under the conditions of given solar irradiation, the thermoelectric (TEG) cold side temperature, cross-section area and number of thermoelements. The calculation technique is verified by experimental setup, which comprises of uncovered flat black painted solar absorber, a heat sink partly submerged on water system and TEG device which was sandwiched in between, 5 commercial TEG devices of different sizes were examined, the steady state TEG open circle voltage and temperatures were measured to evaluate the electric and thermal power experimentally. The data obtained through the calculation technique was validated against the experimental data. The results show that there is an optimum size of the system, decreasing or increasing the size further wouldn’t achieve the optimum performance. The established calculation technique provide the designer (manufacturer) and users with good indication of what TEG size they should use, thus saving the user’s time of examining different TEGs with different aspect ratios (sizes ) and saving manufacturing cost by using less material.